The Effect of Career Development and Work Environment on Job Satisfaction at PT E-Tirta Medical Center Employees Jakarta - Dono Murdiyanto (Journal of Economics and Business UBS, 2019)
This study aims to determine: (1) Effect of career development on employee work satisfaction PT. E-Tirta Medical Center, (2) The influence of work environment on employee work satisfaction of PT. E-Tirta Medical Center, (3) Influence of career development and work environment to job satisfaction of PT. E-Tirta Medical Center. The type of research used is survey. Population in this research is employees of PT. E-Tirta Medical Center. Sampling technique using purposive sampling method with the number of samples of 100 people. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques used to answer the hypothesis is multiple regression. The results of this study indicate that: (1) Variable career development have a positive effect on employee work satisfaction PT E-Tirta Medical Center. This is evidenced from the tcount of 2.864 with a significance value of <0.05, and the regression coefficient has a positive value of 0.224; (2) Work environment variable positive influence on employee job satisfaction at PT. E-Tirta Medical Center. This can be proved from the tcount of 2,864, with significance value of <0.05, and the regression coefficient has a positive value of 0.869; (3) Variable of career development and work environment influence simultaneously to job satisfaction of employees at PT. E-Tirta Medical Center. This can be proved from the value of Fhitung of 59.382 while Ftable for n = 64 of 3.14, with significance <0.05.